Understanding remission in real-world lupus patients across five European countries. (April 2016) - Schneider, M; Mosca, M; Pego-Reigosa, J M; Hachulla, E; Teh, L-S; Perna, A; Koscielny, V; Pike, J; Lobosco, S; Apolone, G
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease associated with increased mortality and significant personal, psychological and socioeconomic consequences. An agreed definition of remission is needed and lacking. We sought to visualize 'remission in SLE' in European patients considered by their physicians to be 'in remission' by comparing the reported symptom burden as reported by treating physicians for patients considered to be 'in remission' and those not considered to be 'in remission'. Data for 1227 patients drawn from a multinational, real-world survey of patients with SLE consulting practising rheumatologists and nephrologists in France, Germany, Italy, Spain, and the UK show that physicians classed their patients as 'in remission' despite a considerable ongoing symptom burden and intensive immunosuppressive medication. Patients considered to be 'in remission' still had a mean of 2.68 current symptoms vs 5.48 for those considered to be not 'in remission' ( p  < 0.0001). The most common symptoms among those seen to be 'in remission' were joint symptoms, fatigue, pain, mucocutaneous involvement, haematological manifestations and kidney abnormalities. The current analysis highlights important ongoing disease activity, symptom burden and immunosuppressive medication in European patients with SLE considered by their treating physician to be 'in remission'. For a further improvement of outcome, there is an urgent need for an international consensus on the definitions for remission among patients with SLE.